Deteksi dan Diferensiasi Virus Kerdil Pisang dengan Teknik PCR-RFLP - Rahma Ayu Priani; Susamto Somowiyarjo; Sedyo Hartono; Siti Subandiyah (Jurnal Perlindungan Tanaman Indonesia, 2010)
Banana bunchy top disease (BBTD) can be caused by the infection of two different viruses, Banana bunchy top virus (BBTV) or Abaca bunchy top virus (ABTV). Both viruses can be transmitted persistently by aphid Pentalonia nigronervosa Coq. The research was conducted to detect and to differentiate the virus bypolymerase chain reaction-restriction fragment length polymorphism (PCRRFLP) techniques. Infected plants were collected from Yogyakarta (Sleman, Yogyakarta city, Bantul, Gunung Kidul, and KulonProgo). Nucleon Phytopure DNA Extraction Kit method was used to extract the total DNA of infected plants. Universal primers of Common DNA region (S-CRF and S-CRR) and specific primers DNA-R (C1-CRF and CI-CRR) were used for PCR amplification. PCR products were analyzed by RFLP technique using the restriction enzyme of DraI. The results reconfirm previous reports that bunchy top disease of banana in Yogyakarta is caused by BBTV. The ABTV was not detected in this present study. Based on the RFLP analysis it was concluded that BBTV collected in this study could be divided into three groups. Group 1 consisted of BBTV isolate from Sleman and Yogyakarta city with two fragments DNA of 400 and 388 bp. Group 2 consisted of isolate BBTV from Kulon Progo and Gunung Kidul with three fragments DNA of 400, 388, and 323 bp. Group 3 consisted of isolate from Bantul with two fragments DNA of 723 and 376 bp. Further study on the complete characteristics of these groups is still needed.